Impact of Motivation Factors on Employee Performance: A Case Study of Panas Pharmaceuticals Pvt. Ltd., Ganapur, Banke - Raj Ghimire, Shiva; Kharel, Sagar; Prasad Timalsina, Dhurba (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: In the highly competitive pharmaceutical industry, understanding and optimizing motivational factors is essential for enhancing employee performance and driving organizational success. This study aims to explore the impact of motivational factors on employee performance at Panas Pharmaceuticals Pvt. Ltd., shedding light on the key drivers of productivity within the organization. Design/methodology/approach: This study employs a positivist research philosophy, utilizing quantitative methods to objectively assess the relationship between the study variables. motivational factors and employee performance at Panas Pharmaceutical Pvt. Ltd. A structured survey design was implemented and data was collected from a purposive sample of 100 employees. SPSS 23.0 was used for analyzing the data. Findings: The findings revealed that all motivational factors including monetary rewards, promotion and fairness, recognition, and job security significantly impact employee performance, with notable differences observed in performance levels among employees based on their motivation levels. Conclusion:The study emphasizes the importance of personalized motivational strategies, such as promotion, fairness, recognition, and job security, in boosting employee performance and enhancing productivity and retention. Implications: This study enriches the understanding of motivation and employee performance by highlighting the critical role of factors such as monetary rewards, promotion and fairness, recognition, and job security in driving productivity, offering valuable insights for management at pharmaceutical companies to implement targeted strategies that enhance employee engagement and performance. JEL Classification: M12, M54, J24, J28